Thermal properties of pillared-graphene nanostructures. Issue 1727 (9th February 2015) - Rifu, M.; Shintani, K.
ABSTRACT: The thermal conductivities of pillared-graphene nanostructures (PGNSs) are obtained using nonequilibrium molecular-dynamics simulation. It is revealed their thermal conductivities are much smaller than the thermal conductivities of carbon nanotubes (CNTs). This fact is explained by examining the density of states (DOS) of the local phonons of PGNSs. It is also found the thermal conductivity of a PGNS linearly decreases with the increase of the inter-pillar distance.